Sleeping Trends & Academic Performance among Medical Students - Humayun Mirza, Rabia Rasheed, Fakhar Zaman, Sehar Javed, Sameen Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Improper sleep and sleeping in the daytime affect intellectual ability of a student and have a undesirable effect on the academic performance. Aim: To define relationship between improper sleep and educational performance. Study design: A Cross sectional study Place & duration of study: 4 months in Lahore Medical & Dental College, Lahore, Pakistan Methodology: This study conducted on 103 medical students. All from fourth year MBBS studying at Lahore Medical & Dental College, Lahore. The students who participated in the study given to complete Pittsburgh Sleep Quality Index (PSQI) questionnaire to find out the quality of their sleep. Their third year annual result obtained to see their academic performance. Results: The no of students that initially participated in the study was 133, however 103 (77%) completed the questionnaires. From the responses received 18.4% students use to be in bed before 11:00 pm, 39.8% went to bed between 11:00 pm and an hour after midnight; and 41.7% went to bed after 2 to 4 am. Most of the students, 75.7% woke up between 5:00 am & 7:00 am and only 1.3% students woke up at or after 8:00 am. There was another class of 21 students, representing 20% reported using sleeping pills. Time taken from fully awake to deep sleep mentioned by 33.0% of the students was less than 15 minutes. Half an hour reported by 46.6% students, 60 and above minutes reported by 20.4% students. Washroom usage at night reported as not causing severe sleep disturbance. 42.7% never have to get up for use of washroom during last one month. 32% and 17.5% were those who have to get up to use washroom once or twice a week. Conclusion: Due to disturbed circadian rhythm of sleep, caused by academic busyness the lack of sleep and its quality caused. . The disturbed sleep in our study was however not associated with academic performance.